TERS: a traffic efficient repair scheme for repairing multiple losses in erasure-coded distributed storage systems. (2018) - Zheng, LiMing; Wang, Xu'an; Tian, XiaoBo; Li, XiaoDong
The high repair traffic and the long repair time of erasure coding have posed a new challenge: how to minimise the amount of data transferred among nodes and reduce the repair time when repairing the lost data. Existing schemes are mostly designed for single node failures, which incur high network traffic and result in low efficiency. In this paper, we propose a traffic efficient repair scheme TERS suitable for repairing data losses when multiple nodes fail. To evaluate the repair cost and the repair time, we provide an implementation of integrating TERS into HDFS-RAID. The numerical results confirm that TERS reduces the repair traffic by 44% on average compared with the traditional erasure codes and regenerating codes. Theoretical analysis shows that TERS effectively reduces the repair time.